Nutrient recycling facilitates long-term stability of marine microbial phototroph-heterotroph interactions - Christie-Oleza, Joseph A. (Nat Microbiol, 2017)
Biological interactions underpin the functioning of marine ecosystems, be it via competition, predation, mutualism, or symbiosis processes. Microbial phototroph-heterotroph interactions propel the engine that results in the biogeochemical cycling of individual elements and are critical for understanding and modelling global ocean processes. Unfortunately, studies thus far have focused on exponentially-growing cultures in nutrient-rich media, meaning knowledge of such interactions under in situ conditions is rudimentary at best. Here, we performed long-term phototroph-heterotroph co-culture experiments under nutrient-amended and natural seawater conditions which showed that it is not the concentration of nutrients but rather their circulation that maintains a stable interaction and a dynamic system. Using the Synechococcus-Roseobacter interaction as a model phototroph-heterotroph case study we show that whilst Synechococcus is highly specialised for carrying out photosynthesis and carbon-fixation it relies on the heterotroph to re-mineralise the inevitably leaked organic matter making nutrients circulate in a mutualistic system. In this sense we challenge the general belief that marine phototrophs and heterotrophs compete for the same scarce nutrients and niche space, but instead suggest these organisms more likely benefit from each other because of their different levels of specialization and complementarity within long-term stable-state systems.